DETERMINATION OF MSME TAXPAYER COMPLIANCE: THE ROLE OF TAX ACCESS, TAX UNDERSTANDING AND TAX RATES IN TOLITOLI REGENCY - Febria, Lisa; Pakawaru, Muhammad Ilham; Parwati, Ni Made Suwitri; Djuri, Phatra Anggana (Jurnal Manajemen Terapan dan Keuangan, 2026)
Abstract Tax compliance is a crucial factor in maximizing national investment, particularly in the Micro, Small, and Medium Enterprises (MSMEs) sector, which significantly contributes to regional economic growth. Although the number of MSMEs continues to increase, the amount of tax paid by business actors does not show consistent growth. This situation indicates that certain factors influence MSME taxes that require empirical research. The purpose of this study is to analyze the factors that influence MSME taxpayer compliance in terms of tax access, tax understanding, and tax rates in Baolan District, Tolitoli Regency. Because the number of MSMEs has not yet reached the ideal tax rate, empirical research is needed at the sub-district level. This study used a quantitative approach with 201 MSME respondents who are required to have a Taxpayer Identification Number (NPWP). Data analysis was conducted using multiple linear regression with SPSS version 27. The results showed that although tax rates did not significantly influence tax compliance, tax access and tax understanding had a positive and significant effect. The implications of this study indicate that improving tax access and tax understanding for MSMEs is important for improving tax compliance. Therefore, the government and tax authorities are expected to increase tax awareness, expand access to tax services, and provide ongoing tax education to MSMEs.  Keywords: Taxpayer Compliance, Tax Access, Tax Understanding, Tax Rates